Level Up Bisnis Tahu & Tempe: Optimalisasi Usaha dengan Aplikasi Credibook - Intisari Haryanti; Ita Purnama; Feni Aryani; Wulan Arlin; Naurah Islami Pasha (INDO PUBLISHING, 2025)
Training on the use of digital technology based on the Credibook application was carried out to improve the financial management capacity of Micro, Small, and Medium Enterprises (MSMEs) tofu and tempeh factories UD. Sumber Hidup in Bima City. The main problem faced is the absence of an adequate bookkeeping system, which has an impact on the unclear cash flow, business planning, and access to formal financing. The training aims to provide a comprehensive understanding of how to utilize the main features of the application such as transaction recording, stock management, monitoring receivables and payables, and automatic financial reporting. The implementation method includes the needs survey stage, socialization of the Credibook application, technical training in recording digital transactions, and evaluation of changes in financial management. The results of the training showed that MSME managers were able to operate the application independently, with skills in recording daily transactions, managing receivables and payables, monitoring stock, and producing automatic financial reports. The use of Credibook has been proven to increase operational efficiency and accuracy of financial recording compared to previous conventional or manual methods. The implementation of this digital system also encourages a change in the mindset of managers towards more professional and data-based business practices. These findings indicate that digitalization of bookkeeping through simple applications can be an effective solution in encouraging the growth and sustainability of MSMEs, especially in the traditional food industry sector.